Combined analysis of sulfur and carbon contents, and foraminifer as paleoenvironmental indicators in tidal flat sediments on Miura Peninsula, Japan. (15th October 2019) - Kitamura, Akihisa; Yamamoto, Yuka; Yamada, Kazuyoshi; Kubo, Atsushi; Toyofuku, Takashi; Nakagawa, Yuki
Abstract: Reconstruction of natural hazards from tidal flat sediments is essential for assessment of coastal hazards, and is based on knowledge of recent sediments. This study therefore examined recent sediments deposited on a narrow, muddy tidal flat on Miura Peninsula, metropolitan Tokyo, Japan, by means of sedimentological analysis, C, N, and S elemental analysis, carbonate content, 137 Cs dating, and analysis of benthic foraminifera (species composition and degree of preservation). 137 Cs profiles of four sediment cores of ∼20 cm in length showed that the sediments were deposited after the release of 137 Cs by the accident at the Fukushima No. 1 Nuclear Power caused by the Tohoku-oki tsunami at March 2011. Results of C/S ratios of mud fractions indicated that the intertidal deposits in the central bay are characterized by low C/S ratios (4.9–11.4) and the bayhead deposits of the upper intertidal and supratidal zones by higher ratios (13.9–24.9). A fluid–mud layer identified in the central bay had the same C/S ratios and carbonate contents as marine sediments, indicating that the fluid-mud deposits probably resulted from resuspension of mud caused by storm-wave action after March 2011. Faunal analysis of benthic foraminifera showed that very low density of foraminifera can be regarded as one of the defining characteristics of fluid-mud deposits. Graphical abstract: Image 1